Analysis of Community Forest Management in Madagascar - World Bank Group (World Bank, Washington, DC, 2015)
The major role tropical forests play in biodiversity and climate change has led the world to search for effective ways to slow down deforestation. Community forest management (CFM) is an example of the broader concept of community-based natural resources management (CBNRM). As part of the decentralization policy in many countries, mainly in Africa and Asia, CFM was expected to promote: (i) a more effective stewardship of the resources by involving the local communities in the management of the resources, and (ii) a more locally-driven development with them tapping most of the derived benefits. The precursors of CBNRM and CFM in Madagascar are the centrally-led compensation-based mechanisms to conservation. Madagascar is one of the first countries in the southern hemisphere to have put in place a legal framework for CBNRM and CFM. The CBNRM implementation process starts with the creation of a local natural resources management group. The government has identified the protection of natural capital and the harnessing of its value as a key pillar in its national development plan for 2015-2019. The plan identifies poor governance as a major constraint to achieving the country’s development objectives. It puts strong emphasis on the roles of both natural capital and the necessity for a more inclusive economy to achieve sustainable development. This report will help the Bank take stock of the nearly two-decades of implementation of the national environmental action plan and provide nation-wide facts that will inform future investment in renewable natural resources management, biodiversity conservation and poverty reduction, and local development in the future. The present work is targeted to decision makers and stakeholders involved in CFM policy with the objective of taking stock of almost 20 years of implementation and advise on future directions in policy formulation. The report is organized as follows: section one presents community forest management (CFM) in Madagascar. Section two provides the result of an impact evaluation analysis conducted on the application of CFM policy. Section three provides an analysis of the legal and institutional aspects of the application of CFM policy in Madagascar. Section four presents recommendations for the short, medium, and longer term. Section five concludes.